Photonic materials displaying direction modulated photoluminescence - Santos, Moliria V. [UNESP]; Maturi, Fernando E. [UNESP]; Pecoraro, Edison [UNESP]; Ferreira, Rute A. S.; Carlos, Luis D.; Ribeiro, Sidney J. L. [UNESP]; IEEE (Ieee, 2019)
The simultaneous integration of a nematic liquid crystalline structure and light emission in a photonic material is attractive for designing novel optical devices. Here we describe the luminescent study of a new optical device that integrates light emission and iridescence through a liquid crystal self-assembly of cellulose nanocrystals and silica. Freestanding composite films with chiral nematic organization were obtained and luminescent species were investigated. The photonic structure plays the role of direction dependent inner filter, causing selective suppression of the light emitted with angle dependent detection.
Keywords: Bacterial cellulose nanocrystals; chiral nematic liquid crystal; iridescence; photonic materials; luminescence; modulated light emission; europium; terbium